Experimental evidence for a genetic basis to differences in aneuploidy in the Pacific oyster (Crassostrea gigas) - Leitao, Alexandra; Boudry, Pierre; Mccombie, Helen; Gerard, Andre; Thiriot-quievreux, Catherine (EDP Sciences, 2001)
Aneuploidy has been previously reported in wild and cultivated Pacific oysters, Crassostrea gigas, and has been shown to be negatively correlated with growth. This is especially important since high variability of growth rate is one of the major problems in the aquacultural production of this species. The existence of a genetic basis for the observed differences in aneuploidy was first investigated through the comparative study of six full-sib families, with mean individual weights ranging from 0.59 to 1.49 g. The slowest growing family was found to have the highest level of aneuploidy. Significant differences in aneuploidy were also found among families when individuals with the same growth rate were sampled. This supports the hypothesis of the existence of a genetic basis for the control of aneuploidy level. Additionally, the possible inheritance of the level of aneuploidy was studied in four full-sib progenies originating from crosses within and between two different populations with contrasting levels of aneuploidy. The limited number of parental oysters (N = 6) in which the scoring of aneuploidy was possible did not allow demonstration of the inheritance of the level of aneuploidy. However, a genetic difference in aneuploidy could be attributed to the origin of the parental populations. As in the first experiment, significant differences in aneuploidy were observed between progenies when sampling individuals of the same weight. Thus, the results of our study of full-sib progenies of C. gigas lend support to the hypothesis of a genetic basis for the level of aneuploidy. Preuve expérimentale d'une base génétique pour les différences de taux d'aneuploïdie chez l'huître creuse (Crassostrea gigas). Des travaux antérieurs ont montré, chez des huîtres creuses Crassostrea gigas sauvages et cultivées, la présence d'aneuploïdie et sa relation négative avec la croissance. En effet, la grande variabilité de croissance est un problème important pour la production aquacole de cette espèce. L'existence d'une base ...